2014
DOI: 10.1108/k-07-2013-0128
|View full text |Cite
|
Sign up to set email alerts
|

Managing knowledge transfer partnership for a rural community

Abstract: Purpose -This paper aims to propose a knowledge transfer partnership (KTP) model, using higher education (HE) students researching in the UK. It is focused on community engagement via charitable trusts, New Opportunities Wirksworth (NOW) & Ecclesbourne Valley Rail (EVR). The researchers designed and implemented a pilot study that explored the potential of a small, yet attractive and active, market town to diversify and regenerate using tourism. This project, which has been funded by the UK Higher Education Inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…KTP's are a well-versed example of UIC's and as evidenced in the literature have a range of impacts for industry, universities and external collaborators as well as economic and academic impact (Penfold, 2007; Wynn and Turner, 2013; Wiltshier and Edwards, 2014). Hewitt-Dundas (2012) highlighted that highly intensive research universities achieve more knowledge transfer whereas less intensive research universities are more likely to focus on their regional economic impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KTP's are a well-versed example of UIC's and as evidenced in the literature have a range of impacts for industry, universities and external collaborators as well as economic and academic impact (Penfold, 2007; Wynn and Turner, 2013; Wiltshier and Edwards, 2014). Hewitt-Dundas (2012) highlighted that highly intensive research universities achieve more knowledge transfer whereas less intensive research universities are more likely to focus on their regional economic impact.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborations such as KTPs which are well documented (Penfold, 2007;Wynn & Turner, 2013;Wiltshier & Edwards, 2014) comprise: the university, company, graduate and government funding; have been around for over 40 years (under different names). Wynn & Turner (2013) argue they are the main mechanism for knowledge transfer providing in excess of £25 million support per year for graduates to work on projects for organisations of all sizes but predominantly SMEs.…”
Section: Technology Transfer and University-industry Collaborationsmentioning
confidence: 99%
“…The reflections on equality of opportunity; the "haves and have nots"; divisions between groups within this community help reinforce the need for detailed plans built around shared values, practices and culture. Although Wirksworth's residents reflect above-average socio-economic and education scores compared to English averages there is very little evidence of capacity building, skills development and embedding new knowledge as part of the original plan (Cooper, 2015;Wiltshier & Edwards, 2014). Skills and training necessary for regeneration are assumed to be in plentiful supply.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that knowledge sharing plays a pivotal role in innovation. In addition, collecting knowledge has a greater effect on product and process innovation than just donating knowledge (Wiltshier and Edwards, 2014). These behaviors vary among departments; academics in some departments find it easier to donate knowledge since staffs share similar values, interests and beliefs.…”
Section: The Knowledge Sharing Impact On Innovation In Educational Organizationsmentioning
confidence: 99%